2015
DOI: 10.1563/aaid-joi-d-13-00220
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Assessment of Mesenchymal Stem Cells Derived From Bone Marrow: Histologic and Histomorphometric Study in a Canine Periodontal Defect

Abstract: The aim of the present study was to investigate an isolation procedure to culture mesenchymal stem cells derived from bone marrow and evaluate their potential in periodontal regeneration. Potential stem cells from bone marrow, aspirated from the iliac crest of nine mongrel canines 1 to 2 years of age, were cultivated. After the examination of surface epitopes of the isolated cells, the total RNA from osteogenic, adipogenic, and chondrogenic cell cultures were analyzed by reverse transcription polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Ten of 22 studies reported quantitative data on histological evidence of new bone, cementum and PDL in the periodontal defect . Most of the remaining studies reported histological quantitative data restricted to new bone and cementum .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten of 22 studies reported quantitative data on histological evidence of new bone, cementum and PDL in the periodontal defect . Most of the remaining studies reported histological quantitative data restricted to new bone and cementum .…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (14 of 22) used dogs and six studies used rats . Finally, merino sheep and minipigs were used in only one study each.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations